The Influence of Religiosity, Academic Pressure, and AI on Academic Fraud through Moral Reasoning - Anisah Fitri S.; Siti Munifah L; Intan Fadilah; Fauzy Nugraha Putra Simbiring; Erwinsyah; Andi Mattulada Amir (Universitas Muhammadiyah Palu, 2026)
This study was to analyze the influence of religiosity, academic pressure, and the use of artificial intelligence (AI) on academic fraud in accounting students. In addition, this study also investigated the role of moral reasoning as a mediating factor. This study conducted a survey of 86 active students of the Accounting Study Program, Tadulako University. WarpPLS is used to analyze data to evaluate direct or indirect influences. The results showed that religiosity and the use of AI had a significant influence on moral reasoning, while academic pressure had no significant influence. Other findings suggest that religiosity, the use of AI, and academic pressure have a direct influence on academic fraud. Moral reasoning has been shown to reduce students' tendency to behave cheating, but it only serves as a mediator between religiosity and academics. In contrast, academic pressure and the use of AI tend to encourage cheating behavior when it is not accompanied by moral awareness and self-control. This condition shows that external elements and technological convenience continue to be the main cause of academic violations, especially in the context of the demands of learning in the era of technology 5.0. The results show that strengthening religiosity, managing academic pressure, and instilling moral values are essential to prevent cheating on campus.